1997
DOI: 10.1038/sj.onc.1201028
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the inactivation of multiple replicative lifespan genes in immortal human squamous cell carcinoma keratinocytes

Abstract: Human keratinocyte immortality is genetically recessive to the normal phenotype of limited replicative lifespan and appears to require the dysfunction of p53 and the cyclin D-Cdk inhibitor p16. In order to test for the inactivation of other candidate replicative lifespan genes in the immortal cells of human tumors, we developed a series of mortal and immortal keratinocyte cultures derived from neoplastic lesions of the head and neck which were amenable to molecular genetic analysis by the loss of heterozygosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
68
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 28 publications
5
68
0
Order By: Relevance
“…The very low turnover of p16 mRNA and the observations of high levels of p16 in late passage number ®broblasts and keratinocytes are both in line with the idea that once p16 expression is induced it will lead to an irreversible exit from the cell cycle as part of the senescence mechanism Loughran et al, 1996;Alcorta et al, 1996). This hypothesis is supported by data suggesting the existence of a gene involved in senescence mapping to the 9p21 locus (Loughran et al, 1994) and the loss of senescence in p16 7/7 mouse embryo ®broblasts .…”
Section: Introductionsupporting
confidence: 73%
“…The very low turnover of p16 mRNA and the observations of high levels of p16 in late passage number ®broblasts and keratinocytes are both in line with the idea that once p16 expression is induced it will lead to an irreversible exit from the cell cycle as part of the senescence mechanism Loughran et al, 1996;Alcorta et al, 1996). This hypothesis is supported by data suggesting the existence of a gene involved in senescence mapping to the 9p21 locus (Loughran et al, 1994) and the loss of senescence in p16 7/7 mouse embryo ®broblasts .…”
Section: Introductionsupporting
confidence: 73%
“…However, there appears to be no correlation between the presence of wild-type Caveolin-1 and allele loss on chromosome 7 since the cell lines COLO357, MDA-MB-231, OVCAR5, and TMSG all demonstrate chromosome 7 LOH which encompasses the CAVEO-LIN-1 locus (unpublished data), but with the exception of COLO357 express wild-type Caveolin-1. This ®nding has also been extended to a series of head and neck squamous cell carcinoma derived cell lines (unpublished data) that we have established and analysed for allele loss (Loughran et al, 1997).…”
Section: Discussionmentioning
confidence: 90%
“…Here, we report the mapping of the gene encoding Caveolin-1 to human chromosome 7q31, in proximity to the marker D7S522, which has been mapped to q31.1. A number of studies has revealed a high incidence of loss of heterozygosity (LOH) at 7q31 in a broad range of human tumours, including carcinomas of the breast (Bieche et al, 1992;Zenklusen et al, 1994a), colon (Zenklusen et al, 1995a), kidney (Shridhar et al, 1997), ovary (Kerr et al, 1996;Koike et al, 1997;Zenklusen et al, 1995b), pancreas (Achille et al, 1996), prostate (Takahashi et al, 1995;Zenklusen et al, 1994b), and stomach (Kuniyasu et al, 1994), as well as squamous cell carcinomas of the head and neck (Zenklusen et al, 1995a, Loughran et al, 1997. The highest frequency of LOH was observed at D7S522.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, p16 has many of the attributes expected of a senescence mediator and it has recently been reported that ®broblasts from p16 nullizygous mice immortalize at a very high frequency, presumably indicative of a failure to senesce (Serrano et al, 1996). Moreover, the higher frequency of p16 deletions and mutations observed in human tumour cell lines as opposed to primary tumours likely re¯ects selection in culture, as a means of escaping senescence, and several studies have provided good evidence for a correlation between loss of p16 function and immortalization (Loughran et al, 1994(Loughran et al, , 1996Rogan et al, 1995;England et al, 1996;Noble et al, 1996;Rezniko et al, 1996). Although the current data imply that this selective pressure may be less critical for mouse cells, there is evidence that the mouse p16 gene also acts as a tumour suppressor.…”
Section: Discussionmentioning
confidence: 99%